Cyberbullying in the Digital Era: A Systematic Review from a Technology Psychology Perspective - Ghina Nisrina; Nazira Irsyani; Pinkan Meilani; Konto Iskandar Dinata (Jurnal Riset Psikologi, 2025)
Abstract. Cyberbullying has emerged as a significant psychosocial phenomenon in the digital era, causing serious psychological impacts on victims. This study aims to conduct a systematic review of current literature on cyberbullying from a technology psychology perspective, identifying forms of cyberbullying, psychological impacts, and digital-based interventions. The systematic review was conducted using SCOPUS, PubMed, PsycINFO, and Google Scholar databases for the 2019-2024 period with keywords including "cyberbullying", "cyberaggression", "online harassment", "psychological impact", and "digital intervention".  Findings reveal six main forms of cyberbullying: flaming, harassment, denigration, outing, impersonation, and trickery. Psychological impacts include depression, anxiety, psychological distress, suicidal ideation, and sleep disorders, mediated by technological factors such as online anonymity and disinhibition effect. Identified digital-based interventions include automated monitoring and detection, digital reporting platforms, website-based interventions, digital awareness promotion, mobile support applications, online counseling, behavioral monitoring, digital peer support networks, and virtual reality for empathy training. This study concludes that cyberbullying requires an integrative approach considering both technological and psychological aspects, with personalized digital interventions showing significant potential in mitigating negative impacts. Abstrak.  Cyberbullying telah menjadi fenomena psikososial yang signifikan di era digital, menimbulkan dampak psikologis serius pada korban. Penelitian ini bertujuan melakukan systematic review terhadap literatur terkini mengenai cyberbullying dari perspektif psikologi teknologi, mengidentifikasi bentuk-bentuk cyberbullying, dampak psikologis, dan intervensi berbasis digital.  Systematic review dilakukan menggunakan database SCOPUS, PubMed, PsycINFO, dan Google Scholar. Temuan menunjukkan enam bentuk utama cyberbullying: flaming, harassment, denigration, outing, impersonation, dan trickery. Dampak psikologis meliputi depresi, kecemasan, tekanan psikologis, ideasi bunuh diri, dan gangguan tidur, dengan mediasi faktor teknologi seperti anonimitas online dan disinhibition effect. Intervensi berbasis digital yang diidentifikasi mencakup monitoring dan deteksi otomatis, platform pelaporan digital, intervensi berbasis website, promosi kesadaran digital, aplikasi mobile dukungan, konseling online, monitoring perilaku, peer support networks, dan realitas virtual untuk empati training. Penelitian ini menyimpulkan bahwa cyberbullying memerlukan pendekatan integratif yang mempertimbangkan aspek teknologi dan psikologis, dengan intervensi digital yang dipersonalisasi menunjukkan potensi signifikan dalam mitigasi dampak negatif.